ARE AFRICA’S POOREST CHILDREN ON COURSE TO AVOID BEING LEFT BEHIND IN POVERTY BY 2030? - Ingutia, Rose (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
This paper examines the performance of key factors influencing the prospect of Africa’s poorest children avoiding being left behind in poverty by 2030 as required by the United Nation’s Agenda for Sustainable Development, a set of sustainable development goals (SDGs) declared in 2015. At that time, sub-Saharan Africa (SSA) was facing both rising debt and deterioration of the fiscal space required to provide resources. Quantitative methods employing descriptive analysis on secondary data are used in this study to compare the trend of child poverty, as represented by under-5 mortality rates (U5MR), both over time and between country clusters. U5MR was chosen because it is an indicator of the well-being of a nation’s children. Countries were “clustered” into quartiles based on their average U5MR between 2000 and 2018. The results indicate marked disparities in U5MR across SSA. No strong association was found between economic growth and U5MR, but good governance, as demonstrated by progress towards achieving the SDGs, correlates with decreases in both U5MR and the incidence of childhood stunting. In the first U5MR quartile, the SDG index score is over 50% in all child poverty indicators under consideration, whereas in the fourth quartile it is below 50%. SSA as a whole performed well in child poverty indicators from 2000 to 2015; however, consideration of the period from 2015 to 2018 suggests that much remains to be done to lift every child out of poverty. Within and across countries, critical areas for immediate attention include: improving sanitation and access to clean water and lowering the prevalence of anaemia and stunting; increasing the rates of exclusive breastfeeding, birth registration, and pre-primary enrolment; and reducing youth unemployment and socioeconomic disparities. Cash transfers to low-income families may help address the added economic insecurity due to COVID‑19 that has left more children vulnerable to child marriage and child labour.